Dynamics of endophytic fungi composition in paris polyphylla var. chinensis (franch.) hara seeds during storage and growth, and responses of seedlings to phytohormones - Peng, Tong; Yang, Tao; Sha, Jie; Zhao, Jiang; Shi, Jianwu (Frontiers in Microbiology, 2025)
IntroductionEndophytic fungi exhibit diverse interactions with plants, from pathogenic to mutualistic symbiosis, and the community composition is regulated by phytohormones. Yet, the composition and dynamics of endophytic fungi in Paris polyphylla var. chinensis (Franch.) Hara (PPC) during fresh seed (FD), sand-stored seed (SSD), and seedling (SS) stages remain unclear. Similarly, the overall impact of phytohormones on the management of endophytic fungal communities is yet to be elucidated.MethodsWe carried out a pot experiment to examine the effects of various stages of PPC seeds and the external addition of three phytohormones, namely, melatonin (MT), strigolactone (SL), and 24-epibrassinolide (BR) on the endophytic fungi of PPC seedlings. This was done through internal transcribed spacer (ITS) amplicon sequencing.ResultsThe study of the endophytic fungal microbiome in FD, SSD, and SS stages of PPC revealed an increased richness and diversity of fungi during the SS stage, with significant changes in community composition observed. We found that Sordariomycetes played a crucial role in this process, potentially contributing to the establishment and growth of PPC seedlings. Additionally, this study investigated the influence of phytohormones on the phenotypic and physiological characteristics of PPC and its endophytic fungal community. Our results demonstrated that MT and SL significantly increased PPC biomass by 69.32 and 15.23%, respectively, while 2 mg/L of BR hindered the growth of PPC roots. MT, SL, and BR not only induced significant changes in the composition and diversity of the endophytic fungal community in PPC but also affected biomass potentially through specific regulation of potential biomarkers. Furthermore, phytohormones were shown to indirectly modify the endophytic fungal community by altering antioxidant system in plants.ConclusionThis study provides novel insights into the dynamic changes of microbial communities in the FD, SSD, and SS stages. Furthermore, the differences among various phytohormones ultimately enhance our predictive understanding of how to directly or indirectly manipulate the plant microbiome to improve plant health.